Adiposity and insulin resistance as mediators between age at menarche and type 2 diabetes mellitus. Issue 5 (May 2020) - Liu, Dechen; Zhao, Yang; Liu, Yu; Sun, Xizhuo; Li, Honghui; Yin, Zhaoxia; Li, Linlin; Wang, Bingyuan; Ren, Yongcheng; Cheng, Cheng; Liu, Leilei; Chen, Xu; et al.
Abstract: Objective: This study aimed to explore the association between age at menarche and type 2 diabetes mellitus (T2DM) and whether the association is mediated by adiposity and insulin resistance (IR) in rural Chinese women. Methods: This cross-sectional study analyzed data for 7, 460 women (median age 56 y) from a rural Chinese area from 2013 to 2014. Data were collected by standardized interviews and anthropometric and laboratory measurements. Adiposity was measured by body mass index (BMI), and IR was measured by the homeostasis model assessment of IR (HOMA-IR) index. Multivariate logistic regression models were used to estimate odds ratios (ORs) and 95% confidence limits (CLs) for the association between age at menarche and T2DM. Mediation analysis was performed to explore the contribution of BMI and HOMA-IR to the association between age at menarche and T2DM. Results: Among 7, 460 women, 840 (11.26%) had T2DM. After adjusting for potential confounding factors, the odds of T2DM with the latest age at menarche 18 years or older versus 13 years was reduced (OR = 0.65, 95% CL: 0.47, 0.91), and age at menarche was negatively associated with T2DM (per additional year of menarche, OR = 0.95, 95% CL: 0.91, 0.99). BMI and HOMA-IR completely mediated the association between age at menarche and T2DM (total indirect effect: OR = 0.973, 95% CL: 0.961, 0.986; direct effect: OR = 0.974, 95% CL: 0.930, 1.021). Conclusions: Late menarche may be negatively associated with T2DM. The potential mechanism is adiposity and IR completely mediating the association between age at menarche and T2DM. Abstract : Supplemental Digital Content is available in the text